Egyptian Treasures - Chambers, Catherine (London A&C Black Publishers Ltd, 2009)
White Wolves are engaging books that children want to pick up, at a range of different reading levels. Eighteen exciting new titles reflect the range of non-fiction texts children will come across in the real world, from guidebooks to cookbooks. They are ideal for topic libraries, and for teaching literacy skills in a curriculum context.
Include Color Illustration and Index
Keywords: Egypt -- Antiquities -- Civilization